Efficient Synthesis of a Regioregular Oligothiophene Photovoltaic Dye Molecule, MK‐2, and Related Compounds: A Cooperative Hypervalent Iodine and Metal‐Catalyzed Synthetic Route. Issue 6 (23rd December 2012) - Dohi, Toshifumi; Yamaoka, Nobutaka; Nakamura, Shota; Sumida, Kohei; Morimoto, Koji; Kita, Yasuyuki
Abstract We have successfully established an efficient route to the core structure of donor–acceptor head‐to‐tail (H–T)‐linked regioregular oligothiophenes, which includes the following key synthetic steps, that is, hypervalent iodine induced direct and regioselective coupling of thiophenes and the use of the obtained bithiophenes as excellent coupling substrates for the Suzuki and Stille couplings. The versatility of this new approach is highlighted in the dramatic improvement of the yield (ca. 59 % overall yield) of MK‐2, a high‐performance organic dye, for photovoltaic applications.